Editorial (English) - Mota, Maurício (Revista de Direito da Cidade, 2016)
DOI: 10.12957/rdc.2016.23698 JOURNAL OF CITY LAW Editorial for vol. 08-3 (2016) The Journal of City Law ranked by MEC / CAPES as Qualis A1, law and registered in the Web of Science, is pleased to publish in this number the article "Land and financial resources for social housing: the solidarity quota in São Paulo's 2014 Master Plan "of Professor Debora Sotto, Attorney of the municipality of São Paulo, PhD in Urban Law from PUC / SP and researcher at the Research Group Urban Environment - GPMAU PUC / SP. This text was presented at the 10th International Conference on Planning, Law, and Property Rights - PLPR 2016 in Bern, Switzerland.